PENGARUH SUASANA DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN DI OBJ COFFEE - Muhammad Firly Margi; Sinthon L. Siahaan (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to analyze the influence of ambiance and brand image on customer loyalty through customer satisfaction at Obj Coffee. The research method used is quantitative with a survey approach. Data was collected through questionnaires distributed to 100 randomly selected Obj Coffee customers. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results show that the café's ambiance has a positive and significant impact on customer satisfaction. Similarly, brand image also has a positive and significant effect on customer satisfaction. Customer satisfaction itself is proven to have a positive and significant impact on customer loyalty. Furthermore, both ambiance and brand image indirectly influence customer loyalty through customer satisfaction as a mediating variable. This study concludes that to enhance customer loyalty, Obj Coffee needs to focus on creating a comfortable café ambiance and improving a positive brand image. Customer satisfaction plays a crucial role as a mediator connecting ambiance and brand image with customer loyalty.